Ammonia sensing behavior of polypyrrole‐bimetallic oxide composites. Issue 7 (27th February 2020) - Malook, Khan; Khan, Hamayun; Shah, Mutabar
Abstract: We report herein the ammonia sensing behavior of polypyrrole‐bimetallic oxide composites (PPy‐V2 O5 ‐MnO2 ) synthesized successfully via a modified chemical oxidation polymerization method in the aqueous medium using FeCl3 .6H2 O as an oxidant. The gas sensing characteristics of the synthesized materials were studied and composite PPy consisting of 4%V2 O5 ‐5%MnO2 (S3) blend was found to be of best with respect to its sensitivity and selectivity toward ammonia gas at room temperature. The effect of various parameters such as bimetallic oxide blend contents, ammonia gas concentration, temperature, and selectivity toward other gases were investigated using S3 as a gas sensitivity material. The material showed good dynamic response toward the target gas. The linearity range, limit of detection, response, and recovery times of S3 was 5 to 60 ppm, 5 ppm, 75 seconds, and 76 seconds, respectively. The splendid results confirmed that the synthesized PPy‐4%V2 O5 ‐5%MnO2 (S3) composite could be a suitable candidate for ammonia detection at room temperature.